2015
DOI: 10.1021/acs.joc.5b00011
|View full text |Cite
|
Sign up to set email alerts
|

Indium(III)-Catalyzed Knoevenagel Condensation of Aldehydes and Activated Methylenes Using Acetic Anhydride as a Promoter

Abstract: The combination of a catalytic amount of InCl3 and acetic anhydride remarkably promotes the Knoevenagel condensation of a variety of aldehydes and activated methylene compounds. This catalytic system accommodates aromatic aldehydes containing a variety of electron-donating and -withdrawing groups, heteroaromatic aldehydes, conjugate aldehydes, and aliphatic aldehydes. Central to successfully driving the condensation series is the formation of a geminal diacetate intermediate, which was generated in situ from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 55 publications
3
38
0
Order By: Relevance
“…Alternatively, Knoevenagel protocols have been developed that use Lewis acids such as LiOH, ZnCl 2 , InCl 3 , TiCl 4 , and NbCl 5 (20)(21)(22) and various heterogeneous solid bases as a catalyst (23). However, the use of heavy metals for the synthesis of food and pharmaceutical products is not desirable because of their toxicity (24).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Knoevenagel protocols have been developed that use Lewis acids such as LiOH, ZnCl 2 , InCl 3 , TiCl 4 , and NbCl 5 (20)(21)(22) and various heterogeneous solid bases as a catalyst (23). However, the use of heavy metals for the synthesis of food and pharmaceutical products is not desirable because of their toxicity (24).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ogiwara et al. have shown that an acetic anhydride used together with indium(III)‐catalyst acts as a promoter of the Knoevenagel reaction . The driving force of the presented method was 1,1‐diacetate, which was generated in situ from an aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…[20] Althought he additiono ft he acetic anhydride to the reaction medium subtly affects the yield of the target product 3a (Table 2, entry 10), its presence completely suppresses formation of undesired bis-adduct 4.R ecently,O giwara et al have shown that an acetic anhydride used together with indium(III)catalysta cts as ap romoter of the Knoevenagel reaction. [29] The driving force of the presented method was 1,1-diacetate, which was generated in situ from an aldehyde. Under the studied reaction conditions with acetic anhydride we did not observe the formation of such an intermediate.…”
Section: Resultsmentioning
confidence: 99%
“…[46] Various catalysts including Lewis acids, zeolites, and different amines have been utilized to catalyze the Knoevenagel reaction. [47][48][49] Recently, the various solidsupported heterogeneous catalysts have been applied to Knoevenagel reaction including Hf (IV) MOF, [50] metalcoordinated, resorcin [4]arene-based molecular trimer, [51] GO-supported PdNi nanoparticles, [52] Zn-based MOF, [53] amino-functionalized Zn/Cd-MOFs, [54] Cu (II)-based metal-organic macrocycle and framework, [55] covalent organic frameworks (COFs) [56] and Core-Shell MOF/ COF. [57] In the present work, Fe 3 O 4 /cellulose/Co-MOF was hydrothermally prepared and utilized as an efficient and cost-effective heterogeneous catalyst for the Knoevenagel reaction under solvent-free conditions.…”
Section: Introductionmentioning
confidence: 99%